Regenerated cellulose from oil palm empty fruit bunch using ionic liquids mixture - Hassin, Noor Syafiqah; Misnon, I. I.; Rasidi, R.; Ahmad, Mohd Rozi; Jasmani, Latifah; Jose, Rajan (Penerbit Universiti Malaysia Pahang, 2022)
This work focused on the synthesis of regenerated cellulose (RC) using ionic liquids (ILs) mixture of 1-Ethyl-3-methylimidazolium acetate (EMIMAc) and 1-Ethyl-3-methylimidazolium chloride (EMIMCl) with oil palm empty fruit bunch (OPEFB) cellulose pulp. The IL-OPEFB mixture were prepare at temperature of 100 oC and stirring speed of 270 rpm; subsequently undergoes dry-jet wet spinning using self-designed water coagulation bath. The morphology, structural, and mechanical properties of regenerated cellulose filament (RCF) were characterized by scanning electron microscope (SEM), optical microscopy, Fourier-transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA) and tensile machine. An Ioncell-type RCF was obtained is showing good mechanical properties with a tensile strength of 160.45 ± 0.699 MPa, a tenacity of 8.774 ± 0.699 cN/tex, Young’s modulus of 83.245 ± 1.183 MPa and 12.92% elongation at break. The RCF had a smooth surface with a round, rigid and hard to break structure are foreseen to have wide applications in sustainable material technology.